Protective coatings for turbine blades - Tamarin, Y. (ASM International, 2002)
This book addresses the problem of surface protection for aircraft engine turbine blades. It is based on the author's 30+ years of work on the development and application of coatings to protect against oxidation and hot corrosion. It describes and details a methodology for optimizing turbine blade surface protection. The distinctions of this book from other publications on this topic include: The performance of protective coatings is assessed and evaluated by the complex interconnections of their chemical and phase composition, structure, and physical-mechanical properties; The properties of overlay coatings are given for the wide range of compositions, including the possible coatings states after their production and long-term service; The principles for calculating the stresses and strains for coated turbine blades are reviewed.
Keywords: Aircraft gas-turbines -- Blades.; Protective coatings.; Gas-turbines -- Materials.; Protective coverings.; elektronické knihy; electronic books